2005
DOI: 10.1007/s11103-005-6163-6
|View full text |Cite
|
Sign up to set email alerts
|

Expressed sequence tags from the Yukon ecotype of Thellungiella reveal that gene expression in response to cold, drought and salinity shows little overlap

Abstract: Thellungiella salsuginea (also known as T. halophila) is a close relative of Arabidopsis that is very tolerant of drought, freezing, and salinity and may be an appropriate model to identify the molecular mechanisms underlying abiotic stress tolerance in plants. We produced 6578 ESTs, which represented 3628 unique genes (unigenes), from cDNA libraries of cold-, drought-, and salinity-stressed plants from the Yukon ecotype of Thellungiella. Among the unigenes, 94.1% encoded products that were most similar in ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
105
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 38 publications
(41 reference statements)
5
105
0
2
Order By: Relevance
“…This gene showed high homology with Hordeum vulgare (Shi et al, 2001). We found the thioredoxin M and H3 type in our database, which have earlier been shown to be associated with (Zouari et al, 2007), Thellungiella (Wong et al, 2005). The GST gene is made full length and the sequence has been submitted in the NCBI GenBank (Accession number EF373062) and further being analyzed for its potential role in salt tolerance.…”
Section: Functional Classification Of Salt Related Estsmentioning
confidence: 94%
See 1 more Smart Citation
“…This gene showed high homology with Hordeum vulgare (Shi et al, 2001). We found the thioredoxin M and H3 type in our database, which have earlier been shown to be associated with (Zouari et al, 2007), Thellungiella (Wong et al, 2005). The GST gene is made full length and the sequence has been submitted in the NCBI GenBank (Accession number EF373062) and further being analyzed for its potential role in salt tolerance.…”
Section: Functional Classification Of Salt Related Estsmentioning
confidence: 94%
“…Arabidopsis genome encodes approximately 5.9% transcription factors (Riechmann et al, 2000). In different halophytes transcription factors form an important component of EST database as evident in Aeluropus littoralis (Zouari et al, 2007), Mesembryanthemum (Kore-eda et al, 2004), Suaeda (Zhang et al, 2001), Thellungiella (Wong et al, 2005). In Thellungiella, Wong et al (2005) have reported that 1% genes belong to transcription or signal transduction elements.…”
Section: Functional Classification Of Salt Related Estsmentioning
confidence: 99%
“…Suggested mechanisms for tolerance to stress and nutrient-limiting conditions include control over stomatal conductance (Inan et al, 2004), greater discriminatory power of K + -and Na + -transport systems (Volkov et al, 2004;Volkov and Amtmann, 2006), and nitrogen utilization efficiency (Kant et al, 2008). However, a genetic basis of the differences in tolerance could only be deduced by attempts at establishing Arabidopsis-like resources and databases (Inan et al, 2004;Taji et al, 2004Taji et al, , 2008Wang et al, 2004Wang et al, , 2006Gong et al, 2005;Wong et al, 2005;Zhang et al, 2008;Oh et al, 2009). Merging the forthcoming T. parvula genome sequence in a three-way comparison that includes Arabidopsis and T. salsuginea (pending; http://www.jgi.doe.gov/ sequencing/why/50029.html) will provide a powerful way to probe for the essence of halophytism, in particular if other crucifer species and ecotypes of wellstudied species are included (Weigel and Mott, 2009;Orsini et al, 2010).…”
Section: Toward the T Parvula Genome Sequencementioning
confidence: 99%
“…A number of tools for comparative molecular characterizations have been developed for T. salsuginea, including tagged mutants, EST collections, and fulllength cDNA collections (Inan et al, 2004;Taji et al, 2004Taji et al, , 2008Wang et al, 2004Wang et al, , 2006Gong et al, 2005;Wong et al, 2005). To date, results of stress challenge studies have identified transcriptome responses that are broadly similar to those shown by Arabidopsis.…”
mentioning
confidence: 99%
“…Thellungiella shares similar morphology and sequence identity with Arabidopsis, thus allowing for the utilization of Arabidopsis genetic information to investigate Thellungiella responses to stress (Inan et al, 2004;Taji et al, 2004;Wong et al, 2005). Several ecotypes of Thellungiella have been collected from Central Asia and North America, indicating the genetic diversity of this plant species (http://www.Thellungiella.org/).…”
mentioning
confidence: 99%